STRUCTURAL DETERMINATION OF L-ASPARAGINASE II OF STREPTOMYCES ALBIDOFLAVUS AND INTERACTION ANALYSIS WITH L-ASPARAGINE AND CEFOTAXIME - TEJASWINI, ACHYUTUNI VENKATA NAGA; RAMESH, MALOTHU (International Journal of Applied Pharmaceutics, 2021)
Objective: L-Asparaginase enzyme possesses a crucial role in the treatment of various hematologic malignancies. The current study focuses on homology modeling and interaction analysis of L-Asparaginase proteins belonging to Streptomyces albidoflavus (S. albidoflavus) with the essential ligand L-Asparagine and subsequent analysis with essential β-lactam antibiotic Cefotaxime. Methods: The process of understanding Asparaginase interactions primarily involved structure determination of WP_096097608, WP_095730301, which is achieved by GalaxyTBM, I-TASSER and SWISS-MODEL. Further, the S. albidoflavus Asparaginase proteins are subjected to GalaxySite and Autodock Vina of PyRx analysis. Results: The GalaxyTBM predicted structures of both the proteins are found promising on various validation studies. The two Asparaginase proteins exhibited high binding affinities of-6.8 and-6.5 kcal/mol with Cefotaxime and-5.1 and-4.9 kcal/mol towards Asparagine. The protein WP_096097608 residues forming hydrogen bonds with L-Asparagine are also analysed to involve in interaction with Cefotaxime on individual docking analysis. Conclusion: The current findings details the two S. albidoflavus Asparaginase proteins affinity towards L-Asparagine, hence can be assessed further for immunogenicity studies. In addition to the above findings, an attempt is made to find the L-Asparaginase binding possibilities with non-metals that identified an essential β-lactam antibiotic Cefotaxime to be an effective inhibitor. This study helps in understanding the interactions of L-Asparaginase with Cefotaxime, as intake of antibiotics between the phases of chemotherapy is observed to treat various infections and also as an antibiotic to microbes that utilize Asparaginase as a vital enzyme.